2017
DOI: 10.1042/bcj20170173
|View full text |Cite
|
Sign up to set email alerts
|

Comparative functional analysis of ribonuclease 1 homologs: molecular insights into evolving vertebrate physiology

Abstract: Pancreatic-type ribonucleases (ptRNases) comprise a class of highly conserved secretory endoribonucleases in vertebrates. The prototype of this enzyme family is ribonuclease 1 (RNase 1). Understanding the physiological roles of RNase 1 is becoming increasingly important, as engineered forms of the enzyme progress through clinical trials as chemotherapeutic agents for cancer. Here we present an in-depth biochemical characterization of RNase 1 homologs from a broad range of mammals (human, bat, squirrel, horse, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 76 publications
0
41
0
Order By: Relevance
“…We note, too, that eRNA secondary structure is thought to be important for its procoagulant activity (Gansler et al 2012). Human RNase 1, which has higher activity against double-stranded RNA than does either mouse RNase 1 or RNase A (Eller et al 2014;Lomax et al 2017), might be better adapted to regulate endogenous eRNA alone.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We note, too, that eRNA secondary structure is thought to be important for its procoagulant activity (Gansler et al 2012). Human RNase 1, which has higher activity against double-stranded RNA than does either mouse RNase 1 or RNase A (Eller et al 2014;Lomax et al 2017), might be better adapted to regulate endogenous eRNA alone.…”
Section: Discussionmentioning
confidence: 88%
“…Excess RNase A was added, and maximum fluorescence intensity (I max ) was measured. Recombinant murine RNase 1 was used to measure k cat /K M = 8.6 × 10 6 M -1 sec -1 , which is indistinguishable from the value at pH 6.4 reported previously (Lomax et al 2017). This value was, in turn, used to estimate the concentration of ribonuclease in mouse plasma with Equation 1:…”
Section: Ribonucleolytic Activity Assaymentioning
confidence: 87%
See 1 more Smart Citation
“…hRNase1 is the human homolog of the family reference protein, bovine pancreatic RNaseA. A comparative evolutionary analysis indicates a divergent role for non-ruminant RNase1 family members that are unrelated to digestion ( 18 , 142 ). Expression of human RNase1 was detected in almost all tissues ( 143 ).…”
Section: The Rnase a Superfamilymentioning
confidence: 99%
“…The authors considered the potential contribution to RNA clearance by eosinophil secreted RNases. Later studies also indicated an RNA scavenging role for pancreatic-type RNases ( 18 , 19 ). In addition, the secreted proteins displayed immuno-regulatory properties that suggest they could participate in the transmission and amplification of local danger signals ( 17 , 20 ).…”
Section: Introductionmentioning
confidence: 97%